2017
DOI: 10.1186/s12889-017-4692-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer survival disparities worsening by socio-economic disadvantage over the last 3 decades in new South Wales, Australia

Abstract: BackgroundPublic concerns are commonly expressed about widening health gaps. This cohort study examines variations and trends in cancer survival by socio-economic disadvantage, geographical remoteness and country of birth in an Australian population over a 30-year period.MethodsData for cases diagnosed in New South Wales (NSW) in 1980–2008 (n = 651,245) were extracted from the population-based NSW Cancer Registry. Competing risk regression models, using the Fine & Gray method, were used for comparative analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(81 citation statements)
references
References 31 publications
2
74
2
Order By: Relevance
“…It is further reassuring that despite our demography suggesting geographic and socioeconomic barriers (Table ), our oncological and surgical outcomes were comparable to other centres and trials . These findings contrast with reports in Australia and other developed countries with public healthcare systems which have found geographic and socioeconomic variations in patient outcomes for rectal cancer …”
Section: Discussionsupporting
confidence: 55%
“…It is further reassuring that despite our demography suggesting geographic and socioeconomic barriers (Table ), our oncological and surgical outcomes were comparable to other centres and trials . These findings contrast with reports in Australia and other developed countries with public healthcare systems which have found geographic and socioeconomic variations in patient outcomes for rectal cancer …”
Section: Discussionsupporting
confidence: 55%
“…The pattern of results was not consistent across States and Territories or across studies applying different geographical classifications. All four studies from New South Wales showed significant geographical disparity in survival rates with poorer survival in non‐metropolitan areas; however, these findings differed when colon and rectal cancer were analysed separately (Cancer Institute NSW, ; Chen et al, ; Jong et al, ; Tervonen et al, ). Four of five studies in Queensland populations showed poorer survival with increasing distance from a major city (Baade, Dasgupta, Aitken, & Turrell, , ; Cramb, Mengersen, & Baade, ; Cramb, Mengersen, Turrell, & Baade, ); however, none of the studies conducted in Western Australia ( N = 3) found significant geographic disparity (Hall et al, ; Martin et al, ; Threlfall & Thompson, ), and mixed results were evident in South Australian samples (Beckmann et al, ; Hocking et al, ; PHIDU, ; Roder et al, ; Singla, Broadbridge, Mittinty, Beeke, & Maddern, ; Wilkinson & Cameron, ) and using national data (Australian Institute of Health & Welfare, , , ; Coory, Ho, & Jordan, ).…”
Section: Resultsmentioning
confidence: 99%
“…RR: Major City (ref); Inner regional: RR 0.90 (0.51-1.56); Chen et al, 2015;Jong et al, 2004;Tervonen et al, 2017). Four of five studies in Queensland populations showed poorer survival with increasing distance from a major city (Baade, Dasgupta, Aitken, & Turrell, 2011aCramb, Mengersen, & Baade, 2011;Cramb, Mengersen, Turrell, & Baade, 2012); however, none of the studies conducted in Western Australia (N = 3) found significant geographic disparity (Hall et al, 2005;Martin et al, 2015;Threlfall & Thompson, 2015), and mixed results were evident in South Australian samples Hocking et al, 2014;PHIDU, 2012;Roder et al, 2015;Singla, Broadbridge, Mittinty, Beeke, & Maddern, 2014;Wilkinson & Cameron, 2004) For instance, there was a trend for the lowest survival rates to be observed for inner and outer regional areas rather than remote or very remote areas.…”
Section: Survival Findingsmentioning
confidence: 99%
“…However, some of the potential explanations mentioned above as well as previous research suggest that not only individual but also contextual and environmental factors might contribute to social inequalities in cancer survival. Indeed, several population‐based studies from different countries have shown that patients living in the most deprived areas experienced lower survival rates than those living in the most affluent ones, for most of the cancer sites …”
Section: Introductionmentioning
confidence: 99%